Causes and outcome of infants admitted with respiratory distress in a tertiary care neonatal unit: A five year review - Verma, Varsha; Ghimire, Deen Dayalu; Jha, Saroj Kumar; Joshi, Suchita Shrestha (Nepalese Respiratory Journal, 2023)
Background: Respiratory distress is a common cause for admission of infants to a neonatal unit. The aim of this study was to analyze the causes of respiratory distress leading to admission in a neonatal unit. Method: This is a 5 year retrospective review of neonates admitted initially with diagnosis of respiratory distress in the neonatal unit of a tertiary care hospital from November 2017 to October 2022. Cases were identified and analyzed using electronic database maintained in the neonatal unit and were cross checked with electronic discharge summaries where necessary. Results: Respiratory distress was found to be the most common cause for admission to the neonatal unit almost comprising of 46% of total admissions. The commonest cause for respiratory distress on admission was found to be transient tachypnoea of newborn (TTN) in term infants and surfactant deficiency respiratory distress syndrome (RDS) in preterm infants. As compared to babies with TTN, who were all discharged home, 18.4% of those with RDS did not survive. The overall mortality of infants presenting initially as respiratory distress was 9.1%. Other common causes for respiratory distress on admission were sepsis, birth asphyxia, shock, congenital heart disease, seizure and polycythemia. Conclusion: Respiratory distress is a common cause for admission to a neonatal unit in both term and preterm infants. Although TTN in term and RDS in preterm are common causes for respiratory distress in newborns, the underlying cause for respiratory distress is diverse and not just limited to the lungs and heart.